2021
DOI: 10.3390/ijms22084069
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis Reveals the Function of the Putative Ester Cyclase UvEC1 in the Pathogenicity of the Rice False Smut Fungus Ustilaginoidea virens

Abstract: Rice false smut is a fungal disease distributed worldwide and caused by Ustilaginoidea virens. In this study, we identified a putative ester cyclase (named as UvEC1) as being significantly upregulated during U. virens infection. UvEC1 contained a SnoaL-like polyketide cyclase domain, but the functions of ketone cyclases such as SnoaL in plant fungal pathogens remain unclear. Deletion of UvEC1 caused defects in vegetative growth and conidiation. UvEC1 was also required for response to hyperosmotic and oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…As detailed above, SnoaL-like cyclases are well described in the antibiotic synthesis in Streptomyces and other bacteria, but not in fungal secondary metabolism. Recently, a putative ester cyclase (named UvEC1) presenting a SnoaL domain has been shown to be important for the virulence of Ustilaginoidea virens but remarkably, its expression is inversely related to toxin production in this pathogen [39]. In conclusion, our results indicate for the first time the involvement of a cyclase gene in the biosynthesis of a polyketide mycotoxin, previously the cyclization step was always associated with the presence of a specific domain in the fungal PKS or NRPS enzymes [41].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As detailed above, SnoaL-like cyclases are well described in the antibiotic synthesis in Streptomyces and other bacteria, but not in fungal secondary metabolism. Recently, a putative ester cyclase (named UvEC1) presenting a SnoaL domain has been shown to be important for the virulence of Ustilaginoidea virens but remarkably, its expression is inversely related to toxin production in this pathogen [39]. In conclusion, our results indicate for the first time the involvement of a cyclase gene in the biosynthesis of a polyketide mycotoxin, previously the cyclization step was always associated with the presence of a specific domain in the fungal PKS or NRPS enzymes [41].…”
Section: Discussionmentioning
confidence: 53%
“…As example, the biosynthetic pathway for aurovertin in Calcarisporium arbuscula seems to be increased by a cyclase protein (aurE), with homology to a SnoaL-like bacterial polyketide cyclase [37,38]. While the involvement of SnoaL-like polyketide cyclases has been clearly demonstrated in the biosynthesis of polyketide antibiotics, only a few proteins with this functional domain have been reported in filamentous fungi [12,39].…”
Section: Discussionmentioning
confidence: 99%
“…This led to the functional identification of various pathogenic genes in U. virens, including iUvt3277, UvCom1, UvPRO1, UvAc1, UvPdeH, SCRE1, SCRE2 (UV_1261), UvBI-1, UvPmk1, UvCDC2, UvCdc3, UvCdc10, UvCdc11, UvCdc12, UvPal1, UvHox2, UvRpd3, UvSlt2, UvATG8, UvZnFTF1, UvMSN2, UvCGBP1, and UvEC1. These genes play important roles in the hyphal growth, conidiation, stress responses, and virulence of U. virens [46][47][48][49][50][51][52][53][54][55]. In the current study, we identified and functionally characterized CCHC-type zinc-finger proteins in U. virens.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, proteomics has been shown to be a useful tool for identifying the differentially expressed proteins involved in fungal infection [ 15 ]. Thus, for example, based on proteome analysis, the ester cyclase UvEC1 was found to be essential for the development and pathogenicity of Ustilaginoidea virens [ 16 ], and pectinases VdPL3.1 and VdPL3.3 were found to be upregulated in the extracellular proteome of V. dahliae in a cotton-containing medium [ 17 ]. Furthermore, a conserved, secreted VdCP1 protein was also identified by proteomics, and the deletion of the corresponding gene reduced the V. dahliae pathogenicity in cotton [ 18 ].…”
Section: Introductionmentioning
confidence: 99%